Contesting crisis narratives amidst climatic breakdown: Climate change, mobility, and state-centric approaches to migration - Kenna Sim-Sarka (Frontiers in Sociology)
Human mobility in the context of climate change is often identified as one of the largest future impacts of the climate crisis. It is often assumed by international institutions and national governments that climate change will drive mass migration movements across borders, leading to a prioritization of research that aims to predict future climate migration to aid border security and the creation of migration policies. This article focuses on knowledge production research concerning around climate-related mobility and how knowledge being produced upholds state-centric approaches to migration and migration management. It argues that by leaving state-centric approaches to migration unquestioned in the name of managing climate-related mobility, national governments and other institutions reproduce inequalities for those who are in the nexus of migration and climate change. This article considers alternative conceptions of mobility and climate change, including the climate mobilities paradigm and decolonial understandings of migration, and how these can shift our analytical focus to more holistic and decolonial understandings of migration.